IMPLEMENTATION OF PROBLEM-BASED LEARNING METHODS IN IMPROVING STUDENTS' UNDERSTANDING OF THE CONCEPT OF TAWHIDIN JUNIOR HIGH SCHOOL - Muhammad Nur Effendi; Muhammad Yusuf (Indonesian Journal of Education (INJOE), 2025)
This study discusses the implementation of Problem-Based Learning (PBL) in improving students' understanding of the concept of monotheism in junior high school. This method was applied to create an active and collaborative learning atmosphere through problem solving that is relevant to students' daily lives. The results showed that the application of PBL was able to significantly improve students' engagement, motivation, and understanding of the basic concepts of monotheism. The learning process began with problem identification, group discussions, solution presentations, and joint reflection. Through this approach, students not only gained cognitive understanding of tauhid theory but also honed their critical thinking, communication, and application of tauhid values in their lives. Thus, the PBL method can be recommended as an effective alternative in tauhid education at the junior high school level to achieve the holistic and contextual goals of Islamic Education.